Influence of Brand Image, Brand Trust and Perceived Product Quality on The Purchasing Decision (Universitas Negeri Semarang, 2022)
This study aims to analyze the influence of brand image, brand trust, and perceptions of product quality on purchasing decision for refill bvlgari extreme sport perfume. This research method uses a type of quantitative research, purposive sampling research sample which amounted to 96 people. Data analysis using multiple linear regression. that the variable brand image (X1) has a positive and significant effect on purchasing decision with a coefficient of 0.277. Then the brand trust variable (X2) has a positive and significant effect on purchasing decision with a coefficient of 0.295. Variable perceived quality (X3) also has a positive and significant influence on purchasing decision with a coefficient of 0.325. While simultaneously or collectively, the variable brand image, brand trust and perceived quality affect purchasing decision. The determination coefficient (R2) is 041,2 or 41.2%. 41.2% of purchasing decision are influenced by brand image, brand trust and perceived quality. The findings in this study are perceived quality is the variable that has the most dominant influence on purchasing decision Bvlgari Sporty Extrem perfume in Semarang City. The conclusion of this study is brand image, brand trust and perceived quality have a significant influence on the sale of perfume products. Results the research use for market improvment of Bvlgari Sporty Extrem perfume in Semarang City.